The multidimensional attractiveness of marathon events: how self-efficacy bridges perception to participation - Wang, Mingtao; Wang, Mengkai; Yuan, Xinyue; Zhao, Xi; Zhang, Yongtao (Frontiers in Psychology, 2025)
IntroductionAlthough marathon events have gained global popularity and align closely with public health objectives, limited research has explored how individuals perceive the attractiveness of these events and how such perceptions influence participation intention. This study introduces the concept of “perceived attractiveness” as a multidimensional evaluation encompassing emotional, symbolic, cultural, and convenience facets related to participation. Drawing upon self-determination theory and self-efficacy theory, the study investigates how perceived attractiveness predicts participation intention, mediated by exercise-related self-efficacy.MethodsA sequential exploratory mixed-methods approach is adopted. Initially, grounded theory is applied to analyze 45 semi-structured interviews with marathon participants, yielding four dimensions of perceived attractiveness: psychological engagement, symbolic and social value, cultural and environmental atmosphere, and participation convenience. These dimensions inform the development of a structured questionnaire, which is subsequently administered to 426 respondents across China. Structural equation modeling (SEM) is employed to examine the hypothesized relationships among the variables.ResultsAll four dimensions of perceived attractiveness significantly predict marathon participation intention. Perceived symbolic and social value exerts the strongest effect, followed by participation convenience, cultural and environmental atmosphere, and psychological engagement. Self-efficacy is found to partially mediate all relationships, indicating that attractive perceptions enhance confidence, which in turn promotes participation intention.DiscussionThe findings suggest that individuals are motivated to participate in marathons not only by intrinsic goals but also by their perceptions of the event’s external characteristics. Perceived attractiveness acts as a cognitive-affective precursor to action, especially when mediated by self-efficacy. These insights contribute to sport psychology literature and offer practical implications for event organizers, educators, and policymakers seeking to foster sustained engagement in physical activity.